The Learning Principles Adopted by the Ida Institute - von Hapsburg, Deborah; Lauritsen, Kirsten (Seminars in Hearing, 2012)
The Ida Institute, a nonprofit educational institute, has developed a set of active and collaborative learning principles that represent a paradigm shift in audiology education designed to foster a better understanding of the human dynamics associated with hearing loss. The Institute emphasizes active listening, active engagement, and reflection through the use of ethnographic videos, mirror exercises, and reflective journaling. Active learning is achieved through unique problem-based approaches, role-playing, case studies, interactive work, and discussions. The methods used by the institute are grounded in active and collaborative learning principles that have been shown to improve student outcomes in learning research. The innovative application of these methods to audiology education allows students to contextualize knowledge—creating lifelong adaptive learners who understand the frameworks for the human dynamics of hearing loss, patient interactions, and the clinical encounter. Institute-developed tools also help audiologists reflect on their own patterns of behavior and facilitate desired changes in their clinical routines.
Keywords: Active learning; reflection; ethnographic